1996
DOI: 10.1016/0014-5793(96)00618-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of myosin heavy chain expression in adult rat hindlimb muscles during short‐term paralysis: comparison of denervation and tetrodotoxin‐induced neural inactivation

Abstract: The extent to which myosin profiles within aduR fast and slow muscles are altered by short-term paralysis remains equivocal. We used an array of specific antibodies to identify adult and developmental MHC isoforms within EDL and soleus muscle fibers, and show a marked multiple expression of MHCs with a general shift towards slower and more energy efficient MHC profiles after 2 weeks of denervation or TTX nerve conduction block. Paralysis also induced marked expression of an embryonic MHC within most EDL cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
60
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 43 publications
16
60
1
Order By: Relevance
“…Other investigators using gel electrophoresis have also reported significant increases in the IIa-IIx and decreases in the I MHC protein bands in the denervated soleus [5,7,14]. Immunohistochemical detection of MHC protein demonstrates that changes in total MHC protein are due to coexpression in the denervated soleus fibers with increases in I/IIx [5,8] and both increases [5] and decreases [8] in I/IIa coexpression.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Other investigators using gel electrophoresis have also reported significant increases in the IIa-IIx and decreases in the I MHC protein bands in the denervated soleus [5,7,14]. Immunohistochemical detection of MHC protein demonstrates that changes in total MHC protein are due to coexpression in the denervated soleus fibers with increases in I/IIx [5,8] and both increases [5] and decreases [8] in I/IIa coexpression.…”
Section: Discussionmentioning
confidence: 78%
“…Those studies that have looked at adult mammals have studied the later stages of denervation (2 weeks to 5 months; [5Ϫ8]) and have provided conflicting results regarding the effects of denervation on MHC protein expression. For example in the 14-day-denervated soleus, protein gel analysis showed a decrease in I MHC and an increase in IIa MHC [7] showed a 25% increase in soleus fibers expressing I MHC and an 88% decrease in fibers expressing IIa MHC [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity and characterization of these mAbs against MHC isoforms have been previously established. The mAbs NOQ7-5-4D is specific to type I MHC (Narusawa et al, 1987;Petrof et al, 1992;Rubinstein and Hoh, 2000), MY-32 to all fast-type MHCs (Havenith et al, 1990;Monemi et al, 2000), SC-71 to type IIa MHC (Schiaffino et al, 1989;Stal et al, 1994;Monemi et al, 2000), ALD-58 to MHC-ton (Shafiq et al, 1984;, BA-G5 to MHC-␣ (Michel et al, 1996), F1.652 to MHC-emb (Michel et al, 1996), and N2.261 to MHC-neo (Michel et al, 1996).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The ␣-cardiac MHC isoform, which is normally expressed in the atrium of the heart, is known to be present in various amounts in some specialized skeletal muscles such as diaphragm (Hamalainen and Pette, 1997), extraocular muscles (Wieczorec et al, 1985;Pedrosa-Domellof et al, 1992;Rushbrook et al, 1994;Rubinstein and Hoh, 2000), and masseter (Bredman et al, 1991;PedrosaDomellof et al, 1992;Stal et al, 1994;Kwa et al, 1995;Korfage et al, 2000) and in the muscle spindles (Michel et al, 1996).…”
mentioning
confidence: 99%